The laws of Solon : a new edition with introduction, translation and commentary /: a new edition with introduction, translation and commentary. (2016) - Leão, Delfim Ferreira; Solon, approximately 630 B.C.-approximately 560 B.C; Rhodes, P. J (Peter John)
No abstract available